2006
DOI: 10.1007/s11267-005-9003-4
|View full text |Cite
|
Sign up to set email alerts
|

Fate and behavior of metal(loid) contaminants in an organic matter-rich shooting range soil: Implications for remediation

Abstract: This study investigates the fate and behavior of lead (Pb), copper (Cu), antimony (Sb), and arsenic (As) in a shooting range soil. The soil samples were collected from the surface (0-15 cm) and the subsurface (15-40 cm and 40-55 cm) of a grassy and wood chip covered impact area behind a firing position. Optical microscopy images indicated significant amounts of corroded bullet fragments and organic wood chips in the surface soil. Analysis by X-ray powder diffraction (XRPD) and scanning electron microscopy elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…Untypical of contaminated soils, however, Pb concentrations were the highest in the very coarse sand fraction in all three range soils, which were 5 -10 times of those in the silt þ clay fraction (Figure 2). Our results were consistent with findings of Dermatas et al (2006a) who reported * 60% of Pb in the coarse fraction (40.425 mm) in shooting range soils. In those soils, there is a lot of fragmentation taking place due to bullets hitting bullets on a continuous basis, resulting in bullet fragments in the coarse fraction.…”
Section: Discussion Pb Concentration Was the Highest In The Very Coasupporting
confidence: 93%
“…Untypical of contaminated soils, however, Pb concentrations were the highest in the very coarse sand fraction in all three range soils, which were 5 -10 times of those in the silt þ clay fraction (Figure 2). Our results were consistent with findings of Dermatas et al (2006a) who reported * 60% of Pb in the coarse fraction (40.425 mm) in shooting range soils. In those soils, there is a lot of fragmentation taking place due to bullets hitting bullets on a continuous basis, resulting in bullet fragments in the coarse fraction.…”
Section: Discussion Pb Concentration Was the Highest In The Very Coasupporting
confidence: 93%
“…However, shooting activities produce the soil contaminated with heavy metals such as Pb from the used bullets (Dermatas et al, 2006). Nowadays, a huge amount of Pb is being deposited in the shooting range soil worldwide at an annual deposition rate of 200 to 60,000 tons (Craig, 1999;Mellor and McCartney, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Shooting ranges are commonly considered as the second largest source of soil Pb after development of the battery industry (Cao et al, 2008). The contamination of shooting range soil with Pb is well documented (Cao et al, 2008;Dermatas et al, 2006;Grubb et al, 2009;Hashimoto et al, 2009a). Most of the studies indicated that Pb levels in the shooting range soils exceed 1% (Chen and Daroub, 2002;Hashimoto et al, 2010) resulting in degrading soil quality, decreasing soil microbial activities and threating to living organisms (Belyaeva et al, 2005;Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of metallic Pb from pellets in soils can be described as: Pb → PbO → PbCO 3 /Pb 3 (CO 3 ) 2 (OH) 2 (Ma et al 2007); the formed Pb carbonates create a protective layer preventing further weathering of the pellets. The weathering rate of Pb is higher in organic soils compared to soils with low organic C contents (even calcite-rich soils) (Dermatas et al 2006) and the transformation of Pb into oxidized species is associated with an increase of soil pH. This is mainly attributed to (1) the consumption of H + ions during Pb corrosion (Pb 0 → Pb 2+ ), (2) the production of OH − ions during Pb carbonate formation, and (3) the subsequent H + consumption during the dissolution of Pb carbonates (Ma et al 2007;Rooney et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Lead concentrations in shooting range soils often exceed 1,000 mg kg −1 (Lin et al 1995;Cao et al 2003a). There have even been evidences of concentrations well above 20,000 mg kg −1 (Lin 1996;Stansley and Roscoe 1996;Dermatas et al 2006). Therefore, the contamination of soils from the close vicinity of shooting ranges presents a serious environmental concern due to the risks associated with groundwater and surface water pollution (Craig et al 1999;Knechtenhofer et al 2003) and contamination of plants growing in the vicinity (Cao et al 2003b;Robinson et al 2008).…”
Section: Introductionmentioning
confidence: 99%